2005
DOI: 10.1111/j.1365-2656.2005.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of wetland fishes: spatio‐temporal patterns synchronized by hydrological disturbance?

Abstract: 1.Drought is a natural disturbance that can cause widespread mortality of aquatic organisms in wetlands. We hypothesized that seasonal drying of marsh surfaces (i.e. hydrological disturbance) shapes spatio-temporal patterns of fish populations. 2. We tested whether population dynamics of fishes were synchronized by hydrological disturbance (Moran effect) or distance separating study sites (dispersal). Spatio-temporal patterns were examined in local populations of five abundant species at 17 sites (sampled five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 39 publications
6
112
0
Order By: Relevance
“…According to Ruetz et al (2005), the main aim of conducting a study in ecological population is to further understand the spatiotemporal pattern from the fluctuated population of species in the certain habitat. Furthermore, the syncronized dynamic of animal population in a largescale become one of high research of interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ruetz et al (2005), the main aim of conducting a study in ecological population is to further understand the spatiotemporal pattern from the fluctuated population of species in the certain habitat. Furthermore, the syncronized dynamic of animal population in a largescale become one of high research of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Of these reasons, the conservation program prior to protecting the fauna species must be conducted and being intensively improved. On the other hand, the utilization of endemic fauna species, which is widely developed its function will become interested studies to the conservation experts, which it means in line with the goal of the conservation program (Ruetz III et al 2005). According to Ajayi (2010) who reported that the utilization of endemic fauna species, which has been further developed its function, showing in well-developed progress in both tropical and sub-tropical regions.…”
Section: Introductionmentioning
confidence: 94%
“…441 Many studies have found that different factors may 442 act together in the formation of synchronous patterns 443 (Ranta et al 1999;Powney et al 2011;Eberhart-Phillips 444 et al 2015;Mortelliti et al 2015). For instance, hydro-445 logical disturbance and dispersal were important mech-446 anisms driving spatio-temporal patterns of Everglades 447 fish populations (Ruetz et al 2005). In our study, at least 448 in one species (Pied Avocet) the distance between lakes 449 and hydroperiod seemed to act together to cause the 450 spatial synchronization of populations.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…individual pools, stream reaches, swamps), and between wetlands and adjacent habitats, are among the most important functional components of estuarine wetlands (Ray 2005, Sheaves 2005). The integrity of estuarine wetlands is maintained by physical connections (Chabrerie et al 2001) that are crucial in determining the extent of water level fluctuations and the temporal duration of aquatic conditions (Ruetz et al 2005), and in allowing mobile species like fish to utilise a range of different habitats often vital for proper nursery ground function (Brockmeyer et al 1997, Sheaves 2005, to enter temporal refuges from predation (Bishop et al 1995, Baker & Sheaves 2005), and to access productive feeding grounds (Shreffler et al 1992).…”
Section: Introductionmentioning
confidence: 99%